Enhancing Fifth-grade EFL Students’ Reading Comprehension through Leveled Narrative Texts and Strategy Instruction. - Aracely Andrea Bastías Gutiérrez (JET (Journal of English Teaching), 2026)
Abstract   This action research study investigated the effectiveness of combining leveled text in the form of narrative readings with explicit reading strategy instruction in improving fifth-grade EFL learners’ ability to identify and extract explicit information from English narrative texts. The study was conducted in a highly vulnerable public school in Hualpén, Chile, where students had limited exposure to English and demonstrated low levels of decoding and reading comprehension, particularly at the literal level. The purpose of the study was to explore how structured, level-appropriate input paired with reading strategy instruction could support early reading comprehension development. Twelve fifth-grade students (aged 10–11, CEFR A1 level) participated in a six-session instructional intervention grounded in the Cognitive Academic Language Learning Approach (CALLA), emphasizing bottom-up strategies such as decoding, keyword scanning, and sentence-level detail identification. Data were collected through pre- and post-intervention comprehension quizzes, a student perception survey administered in Spanish, a focus group, and a teacher reflective journal. Quantitative results showed a meaningful improvement in students’ ability to locate explicit information accurately, while qualitative findings indicated increased motivation, reduced anxiety, and emerging metacognitive awareness of reading strategies. These findings suggest that leveled text combined with explicit reading strategy instruction can effectively strengthen foundational literal comprehension and support early learner autonomy in vulnerable low-input EFL contexts.